Application of the Pyphagor’s Theorem for Correction of Ki and Ka constants of enzyme inhibition and activation - Krupyanko, VI; Krupyanko, PV (Archives of Pharmacy and Pharmaceutical Sciences, 2018)
The analysis of dependence of the length projection of Li vectors of biparametrical inhibited and activated (La) enzymatic reactions from the length projection of vectors of monoparametrical inhibited and activated enzymatic reactions on the basic σ0 plane in three-dimensional coordinate system, allows to deduct the quadratic forms of equations for the correction of the constants of inhibition (ki) and activation (Ka) of enzymes. Examples of correction of constants are given.